The state of the cytokine profile under the conditions of the immobilization stress development - P. Olekshij; M. Regeda; I. Hayduchok (Kazimierz Wielki University, 2023)
The aim of our study is to elucidate changes in the content of pro-inflammatory interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) and anti-inflammatory cytokines interleukin-10 (IL-10) in the blood serum of guinea pigs in the dynamics of experimental immobilization stress.The dynamics of the immobilization stress is accompanied by a pronounced progression of the proinflammatory group of cytokines - TNF-α and IL-6 against the background of declining functional activity of IL-10 at all stages of their formation (3 rd, 5 th and 15 th days) with an advantage on the 3 rd day of the experiment. The data obtained indicate an imbalance of pro- and anti-inflammatory cytokines and impaired cytokinogenesis, which is important for the pathogenesis in immobilization stress.